The Similarities and Differences in Expressing Apology In English And Vietnamese - Hong Hanh, M.A Nguyen Thi (International Journal of Humanities and Education Development (IJHED), 2023)
This paper was conducted to see on the similarities and differences in expressing apology in English and Vietnamese. So as to gather more believable data, the qualitative method including the review of literature and the analysis of some researches related to the topic. Based on the data collected from various types of books and dictionary and internet sources, the author pointed out the similarities and differences in expressing apologies in the two languages and the value of apology culture. As a result, we can improve our communication skills in the daily life.